PERANAN SASTRA INDONESIA DALAM MEMBANGUN KERAGAMAN BUDAYA: PERSPEKTIF SEJARAH - Wilda Fizriyani (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2014)
Dulce et utile is not an odd word in literary world, Dulce et utile is not an odd word to the world of literature, because it is the function of literature. A literary work which is born as the graffiti of the writer has a goal to be entertaining and useful to readers. The benefit is the reader can get many forms of messages, such as moral, religious, even culture. Such as works of Pramoedya Ananta Toer is considered to be influencing the things that are not good for the reader. This can be explained that literary works actually have the ability to affect the